HUBUNGAN KATEGORI TUTUPAN LAHAN DAN SUHU PERMUKAAN MENGGUNAKAN LANDSAT 8 - Fawzi, Nurul Ihsan (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2019)
The global average temperature on Earth has increased by 1 °C over the past 150 years due to climate change. Increasing earth surface temperature also contributes to climate change besides greenhouse gasses. The surface temperature estimation using satellite imagery is important for the analysis of global warming and climate change. The aim of this study is to determine the interaction of surface temperature on the object on the surface of the Earth which is represented by land cover using remote sensing. The data used is the Landsat 8 path/row 121/59 acquisition on July 15, 2018. Processing data to produce land cover information and surface temperature with Planck equation. The result is that each land cover gives a different surface temperature value depending on the thermal capacity and the emissivity of the object. The lowest surface temperature is given by montane forests with an average temperature of 28.4 °C. The highest surface temperature with an average value is owned by a residential object of 34.2°C. The findings in this study, each category of land cover or object has different thermal characteristics even in one type of object. For example, the vegetation area category, oil palm plantations has a higher temperature than primary and secondary forests, with an average temperature difference of up to 3.2 – 3.6 °C. In the technical acquisition of surface temperature using remote sensing, the main factor in the estimation of surface temperature is the presence of cirrus clouds. It is necessary for the initial analysis to assess the presence of cirrus clouds in the image used even though there is no cloud in the visual band. The global average temperature on Earth has increased by 1 °C over the past 150 years due to climate change. Increasing earth surface temperature also contributes to climate change besides greenhouse gasses. The surface temperature estimation using satellite imagery is important for the analysis of global warming and climate change. The aim of this study is to determine the interaction of surface temperature on the object on the surface of the Earth which is represented by land cover using remote sensing. The data used is the Landsat 8 path/row 121/59 acquisition on July 15, 2018. Processing data to produce land cover information and surface temperature with Planck equation. The result is that each land cover gives a different surface temperature value depending on the thermal capacity and the emissivity of the object. The lowest surface temperature is given by montane forests with an average temperature of 28.4 °C. The highest surface temperature with an average value is owned by a residential object of 34.2°C. The findings in this study, each category of land cover or object has different thermal characteristics even in one type of object. For example, the vegetation area category, oil palm plantations has a higher temperature than primary and secondary forests, with an average temperature difference of up to 3.2 – 3.6 °C. In the technical acquisition of surface temperature using remote sensing, the main factor in the estimation of surface temperature is the presence of cirrus clouds. It is necessary for the initial analysis to assess the presence of cirrus clouds in the image used even though there is no cloud in the visual band.